Ordoliberal Articulation of Law-Economy Complex - Lošonc, Alpar; Bunčić, Sonja; Ivanišević, Andrea (Pravni zapisi, 2019)
Various orientations regarding the relationship between law and economics have emerged in recent decades. However, it should be remembered that German ordoliberalism has already formed a definite and striking orientation regarding the aforementioned relationship between law and economics. Also, ordoliberalism can be seen as the ancestor when it comes to the treatment of the aforementioned relationship. This paper intends to follow ordoliberal conceptualization in the field of law and it consists of three parts. The first part describes briefly the emergence of ordoliberalism and presents the reasons for the influence of ordoliberalism on today’s European self-thematization. The second part attempts to show that law is understood as a constituent orientation with respect to the order, a key point of the ordoliberal project, and it explains the meaning of economic constitutionalism. The third part analyzes the importance of competition in the creation of order and it questions how ordoliberalism treats the relation between law and economics, especially in the domain of competition law. The same section explores the issue of defending the identity of ordoliberalism in the context of overall legal and economic dynamics. Key words: ordoliberalism, law and economics, crisis, constitutionalization, economization.